High Prevalence of Metabolic Syndrome among Female Vegetable Market Traders in Hargeisa, Somaliland: Risk Factors and Implications - Fosia Mohamoud; Arthur Kwena; Caleb Nyamwange; Geoffrey Maiyoh (Epidemiology, Biostatistics and Public Health)
Background: Metabolic syndrome, characterized by abdominal obesity and two or more of the following components (fasting blood glucose ≥100 mg/dL, low HDL-cholesterol, high triglycerides, and hypertension), is a common cause of morbidity and mortality. In Somaliland, female vegetable market vendors, who often sit for long hours, face an elevated risk. Aims: This study aims to assess the prevalence and associated factors of metabolic syndrome in this population. Methods: Conducted from December 2020 to April 2021 in Hargeisa’s vegetable markets, this cross-sectional study recruited 291 women using stratified convenience random sampling. Structured questionnaires collected socio-demographic data, while fasting blood samples provided information on blood sugar, triglycerides, and high-density lipoprotein levels. Descriptive statistics and logistic regression were used for analysis. Results: A total of 291 women, aged 21-80 years (mean age 45.3 (12.3) years, participated. The prevalence of metabolic syndrome was 71.8%, significantly higher than global averages. High waist circumference (87.9%, P = 0.00) was the most prevalent component, suggesting unique dietary or lifestyle factors. Notably, no significant association was found between marital status and metabolic syndrome (P = 0.41), contrasting with findings from other regions. Approximately 45% of participants had two components of metabolic syndrome, 40% had three components, and 15% had four components, respectively, indicating a distinct pattern of component distribution. Conclusions: This study found a high prevalence of metabolic syndrome (71.8%) in this population. Key risk factors included older age, high BMI, and increased waist-to-hip ratio, highlighting the need for targeted health interventions and education for this specific occupational group.